Method to Increase Undergraduate Laboratory Student Confidence in Performing Independent Research - Colton E. Kempton (American Society for Microbiology, 2017)
The goal of an undergraduate laboratory course should be not only to introduce the students to biology methodologies and techniques, but also to teach them independent analytical thinking skills and proper experiment design. This is especially true for advanced biology laboratory courses that undergraduate students typically take as a junior or senior in college. Many courses achieve the goal of teaching techniques, but fail to approach the larger goal of teaching critical thinking, experimental design, and student independence. Here we describe a study examining the application of the scaffolding instructional philosophy in which students are taught molecular techniques with decreasing guidance to force the development of analytical thinking skills and prepare undergraduate students for independent laboratory research. This method was applied to our advanced molecular biology laboratory class and resulted in an increase of confidence among the undergraduate students in their abilities to perform independent research.